Assessing the impact of sleep quality on physical function in Chinese older inpatient - Xinmiao Chang; Ying Yuan; Jiling Liao; Qi Zhou; Wenbin Wu (BMC Geriatrics)
Abstract Background Sleep disorders and physical dysfunction are prevalent in the elderly, particularly among hospitalized individuals, yet the relationship between the two remains unclear. Given China’s rapidly aging population, understanding how sleep quality relates to physical function is crucial for informing healthcare practices. This study aims to analyze the relationship between sleep quality and physical function indicators in older patients admitted to internal wards. Methods In this cross-sectional study, the patients admitted in geriatric department were included. Sleep quality was assessed with 8 items Athens Insomnia Scale (AIS-8). Physical function was evaluated from 3 domains: mobility evaluated by Short Physical Performance Battery (SPPB) and gait speed, muscle strength evaluated by grip and chair rises test, balance performance assessed by Timed Up-and-Go test (TUGT). Logistic regression was applied for statistical analyses, adjusting for confounders. Results A total of 545 old patients (≥ 60 years) were included. Those with poor sleep quality (AIS-8 ≥ 6) exhibited a higher likelihood of physical dysfunction, the odds ratio (95% confidence interval) was 1.892 (1.037–3.453) for low gait speed, 1.810 (1.110–2.952) for low grip strength, 2.491 (1.496–4.147) for impaired TUGT. Sleep quality components, particularly maintenance and daytime dysfunction, were linked to physical function indicators. Stratified by age, poor sleep quality was associated with a higher incidence of low grip strength and impaired TUGT in participants ≥ 75 years old. But the association wasn’t seen in patients < 75 years. Stratified by gender, a significant association of sleep quality with impaired TUGT in female population was observed but not for the male population. Conclusions Poor sleep quality was associated with reduced physical function, especially in with advancing ageand in women. Targeted interventions to enhance sleep in the elderly may contribute to maintaining physical function and improve the quality of life of such patients. Clinical trial number Not applicable.